Evaluation of some biophysical characteristics of five silicate solubilizing bacteria isolated from different ecosystems - Vo Hai Duong, Tran; Khoi Nghia, Nguyen (Vietnam Journal of Biotechnology, 2020)
Silicate solubilizing bacteria (SSB) are key microorganisms to solubilize silicate minerals in the soil. Silicon helps to increase the growth and yield of plants and to enhance the environmental stress tolerance capability of plants. The aim of this study was to evaluate the effect of several factors like pH, salinity, and temperature on silicate solubilizing capacity of five selected SSB. Moreover, phosphorus solubilizing, nitrogen-fixing and indole-3-acetic acid (IAA) synthesizing capacity of these five bacteria were also tested. Liquid soil extract medium containing 0.25% Mg2O8Si3 was used in this study. Abilities of bacteria in phosphorous solubility, nitrogen fixation, and IAA synthesis were tested in NBRIP, Burk’s and NBRIP containing 100 mg L-1 tryptophan media, respectively. The results of the study indicated that five SSB showed their high capacity in silicate solubilization at pH 7.0, NaCl 0.0% and 35oC. However, at a concentration of NaCl 0.5%, these five SSB still solubilized well silicate mineral. Moreover, they also solubilized effectively three different insoluble phosphate sources of Ca3(PO4)2, AlPO4 and FePO4 with a range varied between 105.8 and 928.7 mg P2O5 L-1, 33.9 and 49.6 mg P2O5 L-1, and 1.94 and 34.1 mg P2O5 L-1, respectively. They also fixed biologically nitrogen with a range from 1.37 to 5.09 mg NH4+ L-1 after 2 incubation days. Finally, they also showed their ability in IAA synthesis with an amount between 4.85 and 51.5 mg IAA L-1. In short, these five SSB in this study not only had the ability in silicate solubilization but also had other functions in plant growth promotion.